Outcomes of perfluorocarbon liquid vs. posterior retinotomy as adjuncts during pars-plana vitrectomy for the surgical repair of rhegmatogenous retinal detachment: a randomized clinical trial - Ehab Mohamed Elsayed Saad; Hazem Elbadry Mohammed Mohammed; Mohamed Mohamed-Aly Ibrahim; Omar Hassan Salama Selim; Sayed Mostafa Elsayed Abdelhafeez; Ahmed Mohammed Sakr; Fathy Mohamed Abo Elftouh Elsalhy; Ahmed Abdelmohsen Ali Ayoub; Ehab Abdelsamea Alazab; Ehab Tharwat; Tamer Gamal El Sayed Mostafa (BMC Ophthalmology)
Abstract Purpose Rhegmatogenous retinal detachment (RRD) is a sight-threatening condition requiring prompt surgical intervention. Various adjunctive techniques are employed to enhance subretinal fluid drainage and retinal reattachment. This study aimed to evaluate the outcomes of perfluorocarbon liquid (PFCL) versus posterior retinotomy (PR) during pars plana vitrectomy (PPV) for RRD, focusing on anatomical success, visual acuity, intraocular pressure (IOP), and complications. Methods This is a prospective randomized controlled trial that included 58 eyes with RRD, divided into Group A (PFCL, n = 29) and Group B (PR, n = 29). Preoperative assessments included best-corrected visual acuity (BCVA), IOP, axial length, lens status, macula status, and PVR grade. Outcomes were evaluated at 1 week, 1 month, 2 months, and 3 months postoperatively. Primary outcomes included retinal reattachment rates and the number of operations; secondary outcomes included BCVA, IOP changes, complications like cataract development, retinal redetachment, epiretinal membrane (ERM) formation, and single-surgery success. Results Retinal reattachment rates were comparable (76% in Group A vs. 66% in Group B, p = 0.387), as well as the number of operations (p = 0.375). Moreover, BCVA improved significantly in both groups (p < 0.05), with no intergroup differences. IOP increased postoperatively in both groups (p < 0.001), with no significant differences. No differences were observed in cataract formation or retinal redetachment. However, ERM incidence was significantly higher in the PR group (27% vs. 11%, p = 0.049). Conclusion PFCL and PR are effective for RRD repair, with similar anatomical and visual outcomes. However, PFCL may reduce ERM risk, making it preferable in certain cases. These findings guide surgical decision-making and highlight the need for further research. Trial registration The study was retrospectively registered at ClinicalTrials.gov (NCT06919211) on April 4, 2025.